Targeting of a CD8 T cell env epitope presented by HLA-B*5802 is associated with markers of HIV disease progression and lack of selection pressure - Ngumbela, KC; Day, CL; Mncube, Z; Nair, K; Ramduth, D; Thobakgale, C; Moodley, E; Reddy, S; Pierres, C de; Mkhwanazi, N; Bishop, K; Stok, M van der; et al. (AIDS Res Hum Retroviruses, 2008)
In HIV-infected persons, certain HLA class I alleles are associated with effective control of viremia, while others are associated with rapid disease progression. Among the most divergent clinical outcomes are the relatively good prognosis in HLA-B*5801 expressing persons and poor prognosis with HLA-B*5802. These two alleles differ by only three amino acids in regions involved in HLA-peptide recognition. This study evaluated a cohort of over 1000 persons with chronic HIV clade C virus infection to determine whether clinical outcome differences associated with B*5801 (n = 93) and B*5802 ( n = 259) expression are associated with differences in HIV-1-specific CD8 (+) T cell responses. The overall breadth and magnitude of HIV-1-specific CD8(+) T cell responses were lower in persons expressing B*5802, and epitope presentation by B*5802 contributed significantly less to the overall response as compared to B*5801-restricted CD8 (+) T cells. Moreover, viral load in B*5802-positive persons was higher and CD4 cell counts lower when this allele contributed to the overall CD8 (+) T cell response, which was detected exclusively through a single epitope in Env. In addition, persons heterozygous for B*5802 compared to persons homozygous for other HLA-B alleles had significantly higher viral loads. Viral sequencing revealed strong selection pressure mediated through B*5801-restricted responses but not through B*5802. These data indicate that minor differences in HLA sequence can have a major impact on epitope recognition, and that selective targeting of Env through HLA-B*5802 is at least ineffectual if not actively adverse in the containment of viremia. These results provide experimental evidence that not all epitope-specific responses contribute to immune containment, a better understanding of which is essential to shed light on mechanisms involved in HIV disease progression.